Modernization of Saint Pancras and King's Cross Railway Stations in London = Modernizacja dworców kolejowych Saint Pancras i King's Cross w Londynie - Jóźwik, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the renovation and modernization of two London railway stations - St. Pancras and King's Cross. Both stations were built in the middle of the nineteenth century and are an example of industrial heritage. A characteristic feature that distinguishes the two buildings is the metal (iron) structure with a glass canopy. The St. Pancras railway station was characterized by a hall with the largest span in the world, and today is one of the leading examples of using iron in the development of architecture and building structures.
Keywords: dworce kolejowe; konstrukcje z żelaza; modernizacja; Londyn; railway stations; iron structures; modernization; London